2023
DOI: 10.1096/fj.202300295r
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf‐1 promotes vascular smooth muscle cell foam cell formation and atherosclerosis development through CYP4A11/SREBP2/ABCA1

Xiao Li,
Tengfei Zheng,
Yu Zhang
et al.

Abstract: Vascular smooth muscle cells (VSMCs) are considered to be a crucial source of foam cells in atherosclerosis due to their low expression level of cholesterol exporter ATP‐binding cassette transporter A1 (ABCA1) intrinsically. While the definite regulatory mechanisms are complicated and have not yet been fully elucidated, we previously reported that Dickkopf‐1 (DKK1) mediates endothelial cell (EC) dysfunction, thereby aggravating atherosclerosis. However, the role of smooth muscle cell (SMC) DKK1 in atherosclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
(144 reference statements)
0
0
0
Order By: Relevance
“…226 Recently, a study has shown that CYP4A11-derived 20-HETE promotes SMC foam cell formation by regulating SREBP2 activation. 96 Studies have shown that CYP synthase-derived EETs or the overexpression of CYP2J2 significantly inhibit leukocyte recruitment and endothelium-leukocyte interactions in the vascular intima by inhibiting the NF-κB pathway. 97 Further mechanistic studies have shown that EETs in endothelial cells reduce the response of NF-κB to inflammatory factor stimulation by inhibiting the degradation of IκB and preventing the vascular wall adhesion of leukocytes.…”
Section: Cyp Members and Metabolites In Atherosclerosismentioning
confidence: 99%
“…226 Recently, a study has shown that CYP4A11-derived 20-HETE promotes SMC foam cell formation by regulating SREBP2 activation. 96 Studies have shown that CYP synthase-derived EETs or the overexpression of CYP2J2 significantly inhibit leukocyte recruitment and endothelium-leukocyte interactions in the vascular intima by inhibiting the NF-κB pathway. 97 Further mechanistic studies have shown that EETs in endothelial cells reduce the response of NF-κB to inflammatory factor stimulation by inhibiting the degradation of IκB and preventing the vascular wall adhesion of leukocytes.…”
Section: Cyp Members and Metabolites In Atherosclerosismentioning
confidence: 99%